Práticas pedagógicas transformadoras: um olhar sobre a transexualidade com profissionais que fazem parte do comitê territorial de Sobral – Ce - Marques, Francisca Liciane (2024)
This research investigates how the pedagogical practices of professionals who work in schools can have a positive or negative impact on the care provided to trans people in other public schools in Sobral, through field diaries developed during the extension course “A dialogue between gender and transsexuality in childhood and adolescence in a school context”, which had a workload of 30 hours/class. Professionals from Sobral’s Territorial Committee I participated, chosen by the managers of each school. The methodology adopted is based on intervention research, using the field diary as the main instrument for data collection. This method allowed for the connection between the reality experienced and the existing theory, facilitating the understanding of the lessons learned, the interventions carried out andthe reflections developed during the course, without exposing any participant and preserving the ethics of the research. For future reference, this approach encouragesthe production of studies on gender and transsexuality that contribute to the emergence of the voices and bodies of trans people in the educational context. The categories used to conduct the theoretical course and the results were: gender and body, identity and pedagogical practices focused on the theme of transsexuality and school. The discussions and results revealed that disciplinary power and biopolitics perpetuate heteronormative gender norms, making it difficult to include discussionson diversity in teacher training curricula. The difficulty professionals have in making the topic of transsexuality a necessary part of school was highlighted. The participants' resistance to addressing diversity issues highlights the need for continuous learning. Religion also appeared as a factor of extreme influence on the professionals' practices, making it difficult to separate the personal from the professional. In addition, the pathologization in the participants' discourses makes it difficult to welcome trans people into educational institutions and other facilities in thenetwork, evidencing the resistance to discussing inclusive practices.